Model-free Measurement of Exchange Market Pressure - Franc Klaassen; Henk Jager (Tinbergen Institute, 2007)
If there is exchange market pressure (EMP), monetary authorities can use the interest rate and official interventions to offset this depreciation tendency, or they can let the exchange rate change. We introduce a new approach to derive how these three variables should be combined to measure EMP. This approach differs from existing methods, because it is model—free and requires only few assumptions. It implies that the interest rate should be taken in levels, not in the first—difference form typically used, and the level should be taken relative to the interest rate chosen if the country had no external economic objectives. This makes our measure more in line with economic sense. An illustration of EMP measures for the EMS crises in 1992—1993 shows that our adaptation also makes sense in practice.
Keywords: E58; F31; F33; G15; 330; EMP; EMS crisis; exchange rate regime; monetary policy; real interest differential; temporal aggregation